Long COVID Among the Children Admitted to the Department of Pediatrics in a Tertiary Care Centre - Chaudhary, Manoj; Rimal, Hem Sagar; Sah, Love Kumar; Chaudhary, Pankaj (Birat Journal of Health Sciences, 2025)
Introduction: Long COVID is described as signs and symptoms that continue or develop after acute COVID-19. In most cases, long COVID symptoms resolve within 1-5 months. Long‐term health sequels of the COVID‐19 are a major public health concern. However, evidence on post‐acute COVID‐19 syndrome is still limited, particularly for children and adolescents. Objectives: To investigate the prevalence, symptoms, duration and risk factors of long COVID. Methodology: A prospective, observational, longitudinal study was done in BMCTH, a tertiary care centre. Sixty children up to the age of 14-year, diagnosed as COVID-19 by RT-PCR and antibody were included. Follow-up of children were done within 1-3 months and 3-5 months after the treatment of acute COVID-19. Symptoms and duration of symptoms were noted on follow-up after the treatment of acute COVID-19. Results: Out of 60 children, 45 (75%) children were followed within 1-3 months and 3-5 months. Among them, 14 (31.11%) developed long-COVID symptoms. Long COVID symptoms were common in children of one year 5 (33.33%) with predominance of male 9 (36%) compared to female children 5 (25%).The long COVID symptoms were mostly respiratory and neuropsychiatric like cough 7 (50%), difficulty in breathing 5 (35.71%), fever 3 (21.43%), headache 2 (4.28%) fatigue2 (14.28%), Chest/ abdomen pain 2 (14.28%), loss of appetite 1 (7.28%). Severity of acute COVID-19 and multisystem inflammatory syndrome in children were risk factors for long COVID. The symptoms subsided mostly within 3 months. Conclusion: Thirty-one percent hospitalized children developed long COVID; mostly respiratory and neuropsychiatric symptoms. Long COVID symptoms subsided within three months after treatment.